The Development of Thai spelling skill to improve Thai Spelling exercises for Chinese Students learning Thai as a foreign language at Huachiew Chalermprakiet University - Chudech, Pramote (Academic and Research Journal of Liberal Arts (Online), 2021)
The Development of spelling exercising skills for Thai Writing of the Chinese Student studying Thai as a foreign language at Huachiew Chalermprakiet University. Its objective is to create the spelling exercising skills with measurement before and after the exercise. The Group sample is the 15 Chinese Students (3rd and 4th year) studying Thai as a second language in the 2nd semester of the academic year 2019. The research uses the spelling exercises in the spelling section K, D and B,5 exercises for each section, each exercise spends 3 hours practice. The research will use the similar spelling exercise after the practice, then bring both results for comparison. The research’s result found out that the spelling exercising skills has positive development after the practice. It proves that the exercise is effective.